Q&A - Ask Doubts and Get Answers
Q

Find the value of. (iii) 1/2^-2+1/3^-2+1/4^-2

Q3. Find the value of.

    (iii)    \left (\frac{1}{2}\right)^{-2} + \left (\frac{1}{3}\right)^{-2} + \left (\frac{1}{4}\right)^{-2}

Answers (1)
Views
M manish

The detailed explanation for the above-written question is as follows,

This is the exponential form

(a/b)^{m}= \frac{a^{m}}{b^{m}}

So,  \left (\frac{1}{2}\right)^{-2} + \left (\frac{1}{3}\right)^{-2} + \left (\frac{1}{4}\right)^{-2}   

      =\frac{1}{2^{-2}}+\frac{1}{3^{-2}}+\frac{1}{4^{-2}}.......................using this form a^{m}= \frac{1}{a^{m}}

       =2^{2}+3^{2}+4^{2}

      = 4+9+16 

     = 29

Exams
Articles
Questions